Effectiveness of skin protectors and calendula officinalis for prevention and treatment of radiodermatitis: an integrative review - Fabiana Verdan Simões; Valdete Oliveira Santos; Rodrigo Nogueira da Silva; Rafael Celestino da Silva
ABSTRACT Objective: to analyze the effectiveness of skin protectors and Calendula officinalis for prevention and treatment of radiodermatitis. Method: an integrative review conducted at CINAHL, Cochrane Library, Embase, MEDLINE/PubMed, IBECS, LILACS, and Web of Science. The final sample consisted of five studies, four clinical studies and one preclinical. Critical appreciation and narrative synthesis of the findings were carried out. Results: the Cavilon™ skin protector was more effective than Sorbolene (cream with 10% glycerin) and less effective than Mometasone Furoate cream. Calendula officinalis was more effective than Trolamine and essential fatty acids and less effective than Ching Wan Hung® for prevention and treatment of radiodermatitis. Conclusion: data confirm the potential of Calendula officinalis for prevention and treatment of radiodermatitis and point to promising results regarding skin protector use; however, there is a need for further testing as to the effectiveness of such products.